2018
DOI: 10.1097/jtn.0000000000000368
|View full text |Cite
|
Sign up to set email alerts
|

Successful Implementation of an Alcohol Screening, Brief Intervention, and Referral to Treatment Program

Abstract: Devastating effects of alcohol are well established in trauma. To address this, thve American College of Surgeons Committee on Trauma (ACS-COT) requires ACS-verified Level 1 trauma centers to have an active screening, brief intervention, and referral to treatment (SBIRT) program. In 2015, NewYork-Presbyterian/Queens successfully implemented an SBIRT program. Previous studies indicate difficulty in achieving a high level of SBIRT compliance. We explored the effects of a multidisciplinary approach in implementin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…This review also touches on the sustainability of the skills gained by health workers through BI training. To address this issue, the review has identified efforts such as: flexible ongoing training methods, in-person site visits, training materials designed specifically for the unit settings, monthly calls or in-person booster sessions to enhance ongoing implementation efforts [39]. For programs that are developed for Indigenous populations, the review affirms the importance of addressing specific client needs and consultation with Indigenous communities [33,37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review also touches on the sustainability of the skills gained by health workers through BI training. To address this issue, the review has identified efforts such as: flexible ongoing training methods, in-person site visits, training materials designed specifically for the unit settings, monthly calls or in-person booster sessions to enhance ongoing implementation efforts [39]. For programs that are developed for Indigenous populations, the review affirms the importance of addressing specific client needs and consultation with Indigenous communities [33,37].…”
Section: Discussionmentioning
confidence: 99%
“…In the area of delivery of brief interventions by health professionals to their clients, the availability of resources (learning materials, assessment tools and referral guides) and how they were managed within the organisation, and the program's fit with the structural characteristics of the organisation were important [39]. BI delivery needs to be developed as a systems-based practice, with BI and referral to treatment services ideally being active processes.…”
Section: Discussionmentioning
confidence: 99%
“…Given the reported overall small effect of brief interventions4 5 and the generally reported high number of missed patients when screening the entire ED population,7–9 it would be worth considering targeting the screening on patients presenting with factors associated with hazardous alcohol use. Studies performing SBIRT according to this approach reported a lower number of unscreened patients 20 21. Adopting narrower screening criteria may decrease costs and increase specificity, especially when the occurrence of hazardous alcohol use in the total ED patient population is low 6–8 22…”
Section: Discussionmentioning
confidence: 99%
“…The relationships assessed were recognition among professionals, information exchange, and user referral. Previous studies suggest that these relationships are especially relevant in the context of intervention programs implemented by interprofessional teams [ 65 , 66 ]. The relational data were transferred to binary adjacency matrices processed with UCINET software [ 33 ], which was used to calculate centrality measures, the core–periphery structure of the three types of networks in each region, and the level of homophily/heterophily of each actor using as a reference attribute the professional profile of the implementers (psychologists, social workers, and community promoters and support staff).…”
Section: Methodsmentioning
confidence: 99%